2014
DOI: 10.1007/s00270-014-1017-8
|View full text |Cite
|
Sign up to set email alerts
|

Emborrhoid: A New Concept for the Treatment of Hemorrhoids with Arterial Embolization: The First 14 Cases

Abstract: Our case studies suggest that coil embolization of the superior rectal arteries is technically feasible, safe and well tolerated. Additional studies are needed to evaluate the efficacy of this new 'emborrhoid' technique in the management of hemorrhoidal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 23 publications
(32 reference statements)
4
44
0
1
Order By: Relevance
“…And presumed that possible complications could be related to the femoral puncture and to a potential rectal ischemia and suggested that using coils which lead to a non-distal embolization limits the risk of ischemia. Also there was found that patients who previously had rectal surgeries had more developed vascular network of the rectum with more anastomoses [7]. Another retrospective study with 30 patients reported the clinical success of the emborrhoid technique in 72% of patients, with no complications observed.…”
Section: Discussionmentioning
confidence: 86%
“…And presumed that possible complications could be related to the femoral puncture and to a potential rectal ischemia and suggested that using coils which lead to a non-distal embolization limits the risk of ischemia. Also there was found that patients who previously had rectal surgeries had more developed vascular network of the rectum with more anastomoses [7]. Another retrospective study with 30 patients reported the clinical success of the emborrhoid technique in 72% of patients, with no complications observed.…”
Section: Discussionmentioning
confidence: 86%
“…Vidal et al [25] reported a new concept for the treatment of hemorrhoids with arterial embolization. Fourteen patients with disabling chronic rectal bleeding were treated using the emborrhoid technique.…”
Section: Discussionmentioning
confidence: 99%
“…I recently read with great interest the article by Vidal et al The authors treated hemorrhoids with coil embolization of terminal branches of the superior rectal arteries in 14 patients with promising results [1].…”
mentioning
confidence: 99%